The effect of sports participation on the social identity of Chinese university students - Ji, Shuyu; Chen, Shuwei; Yang, Xiannan; Liu, Tongshang; Wang, Xiaolin (Frontiers Media SA, 2024)
Objective: Strengthening youth sports and comprehensively promoting the participation of Chinese university students in sports to enhance their social acceptance are key initiatives for delivering high-quality talent for China’s economic and social development. Methods: Using the China Comprehensive Social Survey as the data source and considering social mentality and social identity, we constructed corresponding statistical models to explore how sports participation influences the social identity (class identity, economic status, and emotional belonging) of Chinese university students. Results: Regarded from a holistic perspective, sports participation can enhance the social identity of college students in all its aspects, and the benefits of sports participation are positively related to its frequency. Under the condition of social mentality, sports participation has a positive effect on the social identity of college students in general and a nonsignificant effect only on certain dimensions. Under the social identity condition, the significance of sports participation for college students’ social identity decreases from lower to higher levels of education. Conclusion: Sports participation significantly enhances the social identity of Chinese university students, and the specific mechanism of the enhancement varies across the social mentality and social identity conditions. In this context, strengthening the role of sports participation in promoting the social identity of college students in the new era is necessary. Deepening the ideological content of physical education courses should be taken as the starting point to enhance the effectiveness of sports participation on the social identity of college students under the condition of social mentality. The effectiveness of sports participation on the social identity of college students with different social identities should be differentiated and enhanced.